Distributed Applications and Interoperable Systems 15th IFIP WG 6.1 International Conference, DAIS 2015, Held as Part of the 10th International Federated Conference on Distributed Computing Techniques, DisCoTec 2015, Grenoble, France, June 2-4, 2015, Proceedings - Bessani, Alysson; Bouchenak, Sara (Computer Communication Networks and Telecommunications, 2015)
This book constitutes the refereed proceedings of the 15th IFIP WG 6.1 International Conference on Distributed Applications and Interoperable Systems, DAIS 2015, held as part of the 10th International Federated Conference on Distributed Computing Techniques, DisCoTec 2015, in Grenoble, France, in June 2015. The 14 full papers and 3 short papers presented in this volume were carefully reviewed and selected from 44 submissions. They deal with topics such as fault tolerance, privacy, resource management, social recommenders and cloud systems.